Radar Talks. (O'Reilly Media, Inc., 2022)
In this edition of Radar Talks, O'Reilly VP of content strategy Rachel Roumeliotis explores the technology trends that will help ensure you're building a cloud-based, data-driven, and AI-enhanced business today that will be a catalyst for your success tomorrow. Learn what you need to know now, illustrated with usage and search stats from the O'Reilly learning platform and insights from O'Reilly's respected editorial team. Recorded on February 1, 2022. See the original event page for resources for further learning or watch recordings of other past events. The O'Reilly Radar Talks series brings you expert opinions on emerging topics through hour-long interactive events. In conversation with some of the industry's top minds, you'll look at the early signals indicating significant trends and new technologies that will shape the future--and discover how to begin forging these technologies now. Share your own predictions and ask your questions while gaining insight into our experts' unique outlooks for the future.